Effect of Health Education Intervention on Diabetes-Related Knowledge of Community Dwelling Adults in Anambra Central Senatorial District, Anambra State - Anyichie, Nonye Eucharia; Okafor, Jerome Okonkwo; Iwuagwu, Tochi Emmanuel (International Journal of Human Kinetics, Health and Education, 2022)
Diabetes mellitus is a chronic metabolic and disabling medical condition that has challenged the health of all ages and cultures in recent time. We assessed the effect of health education intervention (HEI) on diabetes-related knowledge among community dwelling adults (CDAs) in Anambra Central Senatorial District, Anambra State. In a quasi-experiment adopting pre-test post-test non-control group design, a total number of 276 (64 male and 212 female) adults participated. Data collection was done using the University of Michigan diabetes-knowledge Test (UMDKT). Mean, standard deviation and analysis of covariance were used for analyses. The findings reveal that the CDAs who were given HEI had better diabetes knowledge than their counterpart not exposed to HEI, and there was no significant interaction effect of HEI and age, gender and level of education on the mean diabetes knowledge scores of CDAs after HEI. This research proves that health education intervention showed that health education is implicated in adoption of knowledge of diabetes. However, health educators should ensure that adequate information and knowledge of diabetes are imparted on community dwelling adults using suitable channels and medium.